STRATEGIC GUIDELINES OF STATE POLICY IN THE SPHERE OF REGULATION OF THE MILITARIZATION OF THE ECONOMY OF UKRAINE - PRINTS, Volodymyr (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article considers the strategic guidelines of the state policy of Ukraine in the sphere of regulation of the militarization of the economy in the context of a systemic security crisis. The purpose of the study is to determine the conceptual principles and long term directions of state influence on militarization processes in the national economy, taking into account the challenges of external aggression, limited resources and integration aspirations for the global security and economic environment. The dynamics of defense spending, the features of their impact on the budget system, the priorities of the structural transformation of the economy and the institutional ability of the state to carry out effective regulation in this area are analyzed. It is found that the current model of militarization remains fragmentary, excessively dependent on foreign aid and is not supported by a systemic military-economic strategy. The need for the formation of a holistic, predictable and adaptive state policy that would combine mobilization tasks with the strategic goals of sustainable development, innovative growth and security autonomy is substantiated. Key strategic guidelines are identified, in particular: strengthening the role of the national defense industry, developing public-private partnerships in the security sector, increasing domestic production potential, integration into international logistics and technological chains, as well as improving the institutional model of defense economy management. Prospects for further research are associated with assessing the effectiveness of the implementation of these guidelines in the context of international economic cooperation and the formation of new formats of security partnership.